Enhancement of air-side heat transfer performance of additively manufactured condensers - Chan, Yi Qing (Nanyang Technological University, 2024)
This report outlines the investigation of Triply Periodic Minimal Surface (TPMS) designs for enhanced air-side performance novel air-cooled heat condensers. Four types of TPMS, Schwarz-Primitive, Schwarz-Diamond, Schoen-Gyroid, and Schoen-IWP, were produced by “MS Lattice” software and they were numerically investigated using “Ansys Fluent” software. In this study, the thermal performance of 70% and 80% porosity TPMS and Modified Primitive 1 and 2, which were designed by previous Final Year Project students, were investigated. Simulation tests were conducted to obtain the effective thermal conductivity ( ), the heat transfer coefficients, and the pressure drop per unit depth (∆P /H) of each structure. The numerical results showed that structures with 70% porosity have a higher than structures with 80% porosity where Schwarz-Diamond - 80% porosity has the highest of 20.8585 W/m·K while Modified Primitive 1 (80% porosity) has the lowest keff of 9.2337 W/m·K. Modified Primitive 1 (80% porosity) has a lower ∆P HHPthan Modified Primitive 2 (70% porosity) while the heat transfer coefficient comparison for both Modified Primitive structures depends on the boundary conditions applied in the simulations. Modified Primitive 1 has a higher heat transfer coefficient when isothermal conditions were applied to the top and bottom of the structures and a lower heat transfer coefficient when constant heat flux condition was applied to the bottom of the structures. To experimentally investigate these structures, samples of 90 mm long, 40 mm wide, and 15 mm high with a 3.5 mm thickness base were fabricated using additive manufacturing (AM) technology which is a selective laser melting (SLM) technique. Experiments were conducted on all ten samples using the mini wind tunnel setup with a centralised air compressor in Singapore Centre for 3D Printing (SC3DP). The experimental results have shown that Schwarz-Primitive - 80% porosity has the highest ∆P HH of 0.0226 kPa/mm and Modified Primitive 1 has the lowest ∆ HHPof 0.0096 kPa/mm at 2.5 m/s. Schwarz-Diamond - 70% porosity has the highest heat transfer coefficient of 1358.5 W/m2·K and the highest Nusselt number (Nu) of 1125.3 at 2.5 m/s. However, it also has a very high ∆ HH of 0.0204 kPa/mm.